Improving the Ability to Recognize the Concept of Subtraction in Group B Children through Bowling Games at RA Athohiriyah - Ida Saprida; Ida Hamidah (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the ability to recognize the concept of subtraction in early childhood, especially children in Group B at RA Athohiriyah, Limo, Depok, through bowling game activities. The background of this study is the low understanding of children towards the concept of subtraction as seen from the results of initial observations, where most children have not been able to subtract correctly and are still confused about distinguishing between the concepts of addition and subtraction. This study is a Classroom Action Research (CAR) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 20 children in Group B in the 2017-2018 academic year. Data were collected through observation, interviews, documentation, and assessment of children's performance. The results of the study showed that the implementation of bowling games can significantly improve children's ability to recognize the concept of subtraction. In cycle I, children who achieved the learning completion criteria were 55%, increasing to 85% in cycle II. Children become more enthusiastic, active, and understand the concept of subtraction concretely through fun and interactive play activities. Thus, bowling games are proven to be effective as a learning medium that can help children understand basic mathematical concepts contextually and enjoyably. This study recommends the use of educational games in learning mathematical concepts for early childhood, in order to create a more meaningful and enjoyable learning atmosphere.